Role of Resection of the Primary Pancreatic Neuroendocrine Tumor in the Multidisciplinary Treatment of Patients with Unresectable Synchronous Liver Metastases: A Case Series - Kondo, Naoko Iwahashi; Ikeda, Yasuharu; Maehara, Shin-ichiro; Sugimoto, Rie; Nishiyama, Ken-ichi; Sakaguchi, Yoshihisa (JOP. Journal of the Pancreas, 2013)
Context Liver metastases have often existed in patients who have pancreatic neuroendocrine tumors (pNETs) at the time of diagnosis. In the management of patients of pNETs with unresectable liver metastases, the clinical efficacy of surgery to primary pancreatic tumor has been controversial. We presented four patients who were treated with resection of primary pancreatic tumor, trans-arterial hepatic treatment and systemic therapies. We reviewed literatures and discussed about role of resection of primary pancreatic tumor in the multidisciplinary treatment. Methods We retrieved medical records of patients who had been histopathologically diagnosed as pNETs at our institution between April 2000 and March 2006, and found 4 patients who had pNETs with unresectable synchronous liver metastases and no extrahepatic metastases. All patients received resection of primary tumor. Patients’ demographics, pathology, treatment, short- and long-term outcome were examined. Results In short-term outcome analysis, delayed gastric emptying was developed in one patient who received pancreaticoduodenectomy. There were no other significant postoperative complications. As for long-term outcome, two patients who received distal pancreatectomy, sequential trans-arterial treatments and systemic therapies could survive for long time relatively. They died 92 and 73 months after the first treatment, respectively. One patient who received distal pancreatectomy and trans-arterial treatment died from unrelated disease 14 months after the first treatment. Another patient who received preoperative trans-arterial treatments and pancreaticoduodenectomy rejected postoperative trans-arterial treatment, was treated with systemic therapies and died 37 months after the initial treatment. Conclusions Resection of primary pNETs would be considered as an optional treatment for the selected patients who had unresectable synchronous liver metastases in the process of the multidisciplinary approach. Image: Microscopic images of three patients of pNETs.